Use of point-of-care lung ultrasonography in the critical care setting as an aid to identifying the correct diagnosis in an acutely desaturating patient with COVID-19-related acute respiratory distress syndrome. Issue 3 (16th March 2021) - Lock, Chris; Nix, Catherine M
Abstract : A 64-year-old man was intubated and ventilated for COVID-19-associated acute respiratory distress syndrome. He had a background history of chronic obstructive pulmonary disease and ischaemic heart disease. His oxygen saturations dropped rapidly to 80% on day 9 of ICU admission. Chest auscultation revealed absent breath sounds over the left upper chest which raised suspicions for pneumothorax, of which a small stable left apical pneumothorax was documented on a recent CT scan of the thorax. Point-of-care ultrasonography was performed prior to attempting chest drain insertion which demonstrated sliding pleura on the left side (GE Healthcare model: Vscan Extend—display: 5 inches, 720×1280 pixels resolution, sector probe—broad bandwidth: 1.7–3.8 MHz, 24 cm penetration and linear probe—broad bandwidth: 3.3–8 MHz, 8 cm penetration). A portable chest X-ray was obtained which demonstrated left upper lobe collapse secondary to mucus plugging. The mucus plug was successfully suctioned from the patient's airway using bedside bronchoscopy subsequently improving the patient's oxygen saturation. A follow-up chest X-ray and CT scan of the thorax demonstrated interval resolution of the left upper lobe collapse. While expansion of his existing pneumothorax was first on the list of differential diagnoses, the use of ultrasonography early in the patient's assessment ensured it was ruled out prior to attempting chest drain insertion, thus prompting the acquisition of the chest X-ray which subsequently demonstrated the left upper lobe collapse as the correct diagnosis.